2020
DOI: 10.1111/tan.14092
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies to target the humoral alloimmune response

Abstract: Antibody-mediated rejection (ABMR) represents a major cause of late allograft loss in solid organ transplantation worldwide. This process is driven by donor-specific antibodies (DSA), which develop either de-novo or, in sensitized patients, are preformed at the time of transplantation. Effective targeting of ABMR has been hampered by a lack of robust randomized controlled trials (RCT), required for the regulatory approval of new therapeutics. In this review, we discuss the evidence behind the present "standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…DSA target graft cells, resulting in complement activation and inflammatory reactions with the recruitment and activation of neutrophils. These phenomena induce graft tissue damage ( Suchanek and Clatworthy, 2020 ; Oellerich et al., 2021 ) ( Figure 2 ).…”
Section: Graft Rejection Mechanismsmentioning
confidence: 99%
“…DSA target graft cells, resulting in complement activation and inflammatory reactions with the recruitment and activation of neutrophils. These phenomena induce graft tissue damage ( Suchanek and Clatworthy, 2020 ; Oellerich et al., 2021 ) ( Figure 2 ).…”
Section: Graft Rejection Mechanismsmentioning
confidence: 99%
“…De novo generation of DSAs is a consequence of naïve B cell activation following alloantigen recognition via B cell receptor (BCR). Alloreactive B cells can either differentiate into short-lived (extrafollicular) plasma cells or contribute to memory compartment residing in germinal centers (GC) of lymph nodes [ 110 ]. Extrafollicular plasmablasts are the source of low-affinity IgM antibodies.…”
Section: Sev In Solid Organ Transplantationmentioning
confidence: 99%
“…27 Moreover, systemic inflammation is accompanied by immune activation that may promote the production of de novo DSA. For example, among many effects, IL-6 is essential for B cell differentiation, antibody production and the generation of long-lived plasma cells 28,29 Previously, we have shown that pre-existing chronic systemic inflammation at the time of transplantation predicts delayed graft function and all-cause mortality in kidney transplanted recipients. 30 In the present study, our ambition was to explore mechanisms that link systemic inflammation at the time of transplantation with mortality in the following years.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Moreover, systemic inflammation is accompanied by immune activation that may promote the production of de novo DSA. For example, among many effects, IL‐6 is essential for B cell differentiation, antibody production and the generation of long‐lived plasma cells 28 , 29 …”
Section: Introductionmentioning
confidence: 99%